Overview of credit risk portfolio management - Rodr(acute)iguez Valladares, Mayra; Safari eBooks ([S.l.] : FT Press Delivers, 2011)
"This video course offers a complete introduction to essential credit portfolio risk management techniques, carefully examining and comparing several of the most widely used models and approaches. Leading consultant and New York Institute of Finance instructor Mayra Rodr(acute)iguez Valladares thoroughly reviews the use of credit derivatives and other risk mitigation methods as part of a coherent and effective credit portfolio risk management program. Rodr(acute)iguez Valladares shares deep insights drawn from her extensive experience as a consultant, practitioner, and instructor working with leading private banks, central banks, and regulators worldwide. She begins by illuminating the relationship of credit risk to other risks faced by financial institutions, including market risk, operational risk, and liquidity risk. Next, she presents an integrated view of risk management, including a concise explanation of the evolving roles of credit reporting agencies. Coverage also includes a definition and discussion of internal risk rating systems, a practical explanation of credit risk measurement in relation to the widely-used Value-at-Risk (VaR) approach, a clear explanation of the Options Theoretic Model of credit risk, and a review of the key mitigants of credit risk. Participants will gain deeper insights into exposure, default probability, and expected loss; the Risk-Adjusted Return on Capital (RAROC) methodology; CreditMetrics; options pricing of credit risk, and much more."--Resource description page.
Title and publisher from title screen.
Date of publication from resource description page (viewed Oct. 17, 2011).
"New York Institute of Finance virtual class"--Title screen.
Keywords: Credit -- Management; Portfolio management; Risk management; Electronic books